2-x/3=-2

Simple and best practice solution for 2-x/3=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-x/3=-2 equation:



2-x/3=-2
We move all terms to the left:
2-x/3-(-2)=0
We add all the numbers together, and all the variables
-x/3+4=0
We multiply all the terms by the denominator
-x+4*3=0
We add all the numbers together, and all the variables
-1x+12=0
We move all terms containing x to the left, all other terms to the right
-x=-12
x=-12/-1
x=+12

See similar equations:

| 4x+5(3x-11)=2 | | 4x–2+3x–7=–51 | | 3​+4​y​=17 | | 5-4/3x=11-2/3x | | 3x-8=-×+40 | | 190=79-u | | -(6x-3=-29+2x | | 6*2.5=g | | 3​​+4​y​=17 | | 8=2(z-2) | | 30x-10x-25+4x-5+15x=48 | | 12z-8=100 | | -5-6r=7 | | ‐3–6(x-7)=42–6x | | 6x-3=2(3x-1) | | 154-v=220 | | -7y-8y+2=-13 | | 5.5m=-70 | | r-11/4=-1 | | .15m=22+.11m | | 4(3g-1)=12g | | 16-2q=-q | | 5r+10r+-11=19 | | c–5=7 | | -8n+10=98 | | -14+24=-2(x+3) | | n4-1=10 | | -2(2x+4)-8=8 | | -5r-5(1+3r)=9(7-6r) | | 3d-2d+1=17 | | (3)(x)=(5)(9) | | -6=-8+2y |

Equations solver categories